Spatiotemporal variability and functional redundancy obscure effects of urbanization on strawberry pollinators - Kyla D. Schulte; Caleb J. Wilson; Anna Tawril; Mary A. Jamieson (Ecosphere)
Abstract Pollination services across rural–urban gradients may vary as land cover and other environmental attributes differentially influence pollinators. Most studies examining crop pollination, however, have been conducted in rural environments, while research in urban areas has lagged behind despite growing interest in urban agriculture. In this study, we hypothesized that increased urbanization would alter pollinator community composition due to a reduction in natural areas within the surrounding landscape, potentially decreasing pollinator abundance. To evaluate this hypothesis, we conducted a three‐year study using strawberries as a focal study crop. We characterized the abundance, diversity, and community composition of bees across 10 farms along a rural–urban gradient in Michigan, USA. Across sites and years, we found that urbanization, measured as impervious surface cover, had no consistent effect on overall bee abundance and diversity. However, urbanization differentially influenced certain taxa, namely, Halictini which was positively associated with more urban environments in year one and Ceratinini which was negatively associated with more urban environments in year three. Sweat bees and small carpenter bees were the most frequent strawberry flower visitors across sites and years, although honey bees were dominant at rural sites in year one. We observed 61 bee species visiting strawberry flowers, most commonly Lasioglossum, Ceratina, and Augochlorella species. Most bee species were generalist foragers that visited many flower species within each site. Variation in strawberry floral visitors across years appeared to be driven by shifts in flower phenology, especially in year one when flowering was delayed due to the practice of flower removal to increase yield. Our study demonstrates the importance of wild bees, especially native species, as pollinators in urban agriculture and illustrates how habitat context shapes bee communities.